Assessing New Wars Theory in The Post-Arab Spring Era: The Libyan and Yemeni Wars (2011-2020) - El-Sherif, Shady (AUC Knowledge Fountain, 2022)
Mary Kaldor’s “New Wars” theory which was first published in 1991 argues that warfare has changed after the Cold War with the growing globalization and the rise of violent non-state actors. According to the theory, globalization augmented certain problems that are considered the main causes of these “new wars” such as; state fragility/failure, identity politics, and war economy methods which all account at present for the continuation of conflicts, especially in the MENA region with more civilian casualties. To assess this theory, I am using a comparative case study methodology with a historical process-tracing approach for the Yemeni and Libyan wars from 2011 until 2020. This comparative analysis seeks to either validate the relevance of the theory in the post-Arab Spring era or refuse Kaldor’s argument that modes of warfare have changed. The reason for choosing both cases is that conflicts in both states are being directed mostly by non-state actors rather than sovereign states, and they became more brutal against civilians and much longer. Hence, after the assessment, we should see if the conventional understanding of war and peacebuilding that prevailed in the pre-Cold War era should be reconsidered to enable efficient and decisive policies to control and -hopefully- stop these "new wars" or not.